Determining Qibla Direction of Mosques in Jambi Province: Method, Conflict, and Resolution - Zufriani, Zufriani; Suhar AM; Hermanto Harun (International journal of technology and education research, 2023)
The development of technology and science has an essential role in human life, as well as concerning worship, such as determining the Qibla direction. However, some mosques still determine the Qibla direction based on estimates or follow the Qibla direction of existing mosques so that the Qibla direction is inaccurate or does not point directly to the Kaaba. The Qibla direction of mosques in Jambi Province is measured using a compass instrument, and they believe that the Qibla direction is to the west. Astronomically, the north direction indicated by the compass is the earth’s magnetic north, not true north, so it is necessary to re-measure to ensure the Qibla direction of mosques which is considered problematic to avoid conflict in the community. This paper explores the methods of determining the Qibla direction of mosques in Jambi Province. This paper aims to determine the method of determining the Qibla direction of mosques in Jambi Province. This research is normative-sociological. There are two sources of data, namely primary data and secondary data. This study took the research object in three districts, namely Kerinci Regency, East Tanjung Jabung Regency and Bungo Regency. Data collection techniques used are observation, interviews, and documentation. The data analysis technique is data condensation, data presentation, and drawing conclusions. The results of the study show that there are several methods for determining the Qibla direction of mosques in Jambi Province. Facing him is obligatory and is one of the eight conditions for the validity of prayer.